(untitled) (Bangladesh Journal of Plant Taxonomy, 2014)
Amorphophallus Blume ex Decne. sect. Amorphophallus in India is revised. It is the smallest of the three sections in India with five species, viz. A. hirsutus Teysm. & Binn., A. kachinensis Engl. & Gehrm., A. longistylus Kurz, A. napalensis (Wall.) Bogner & Mayo and A. paeoniifolius (Dennst.) Nicolson. Amorphophallus paeoniifolius is the widely distributed species in India with two varieties, viz. A. paeoniifolius var. paeoniifolius, and var. campanulatus (Decne.) Sivad. Amorphophallus longistylus is the only species of the section endemic to India. DOI: http://dx.doi.org/10.3329/bjpt.v21i2.21349 Bangladesh J. Plant Taxon. 21(2): 105-120, 2014 (December)